Analisis Pengaruh GDP Per Kapita, Financial Development, Energy Use, dan Populasi Usia Produktif Terhadap Emisi CO2 di Indonesia - Sherin Alifah; Amin Pujiati (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Carbon dioxide (CO₂) emissions are a form of negative externality from economic activity and development, with serious implications for climate stability. Indonesia ranks 9th as the country with the highest carbon dioxide (CO₂) emissions according to the International Energy Agency (IEA) in 2021. Indonesia's total CO₂ emissions in that year will be around 619 Mt CO₂e. The increase in CO₂ emissions in Indonesia is inevitable, as it is influenced by various structural and economic factors. This study aims to identify factors that influence the increase in CO₂ emissions and analyze the long-term influence of the variables GDP per capita, Financial Development Index, Energy Use, and Productive Age Population (15-64 years) on CO₂ emissions in Indonesia. The analysis method used is Fully Modified Ordinary Least Squares (FMOLS). The results showed that all independent variables have a positive and significant effect on CO₂ emissions in the long run. This means that every 1% increase in the independent variables can increase total CO2 emissions in Indonesia. GDP per capita variable can increase by 0.04% CO2 emissions, Energy use contributes 0.68% to CO2 emissions. Productive age population (15-64 years) can affect 0.12%. Meanwhile, Financial Development in scale can have an effect of 0.30% on CO2 emissions. . This finding indicates that CO2 emission reduction policies need to focus on energy use efficiency and sustainable economic growth.